Investigating teachers’ attitude toward digital literacy in EFL classroom - Bambang Widi Pratolo; Hana Amri Solikhati (Journal of Education and Learning (EduLearn), 2021)
Digital literacy has been a major concern for people involved in education sectors including students, teachers and policy makers. Thus, to make the education in this era more effective to help reach the goals, English teachers should be digitally more literate. The aims of this study are; 1) to find out how the digital literacy was implemented; 2) to determine teachers’ attitude in implementing the digital literacy; 3) to scrutinize the challenges; and 4) the actions they took to cope with them. Employing a qualitative research method, this study used a semi-structured interview and classroom observation to collect the data from two EFL teachers at a junior high school in Temanggung, Central Java, Indonesia as the subjects. The data were then identified, categorized, organized, coded, described and reported following the thematic analysis. The findings showed that they used computer and smartphone to search for digital information. The teachers exhibited positive attitudes in the use of digital literacy for EFL teaching. They used syllabus as a major consideration, understood their position as teachers, developed effective teaching, implemented multiple literacy and improved the four language skills. However, issues related to lack of technology, students’ background, lack of time and limited budget were acknowledged as hindrances in digital literacy implementation. As a strategy, teachers have therefore developed an early planning and support plan to deal with these challenges. Finally, this study suggests the need to develop teachers' technical facilities, technological pedagogy, and policy makers to give digital literacy more attention.